2020
DOI: 10.37018/jfjmu.661
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and types of congenital heart disease in neonates: A cross-sectional study from large public sector hospital of Karachi, Pakistan

Abstract: Background: Congenital heart disease (CHD) is one of the frequent congenital health issues in neonates. Early diagnosis is a key factor to combat this problem. This study aims to assess the frequency and common types of CHD among neonates presenting to a tertiary care hospital, Karachi. Patients and methods: This descriptive cross-sectional study was conducted in a Neonatal Intensive Care Unit (NICU) of National Institute of Child Health (NICH), Karachi from March to September 2017. All neonates of gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similarly a study by Lynch A et al 20 showed that TGA was the most common cyanotic CHD in prenatal as well as post natal period. TGA was the most common cyanotic CHD in neonates in similar studies carried out in Karachi 21 and Abbottabad 3 Pakistan. In our study TGA was the second most common CCHD noted in 23 % of cases.…”
Section: Resultsmentioning
confidence: 72%
“…Similarly a study by Lynch A et al 20 showed that TGA was the most common cyanotic CHD in prenatal as well as post natal period. TGA was the most common cyanotic CHD in neonates in similar studies carried out in Karachi 21 and Abbottabad 3 Pakistan. In our study TGA was the second most common CCHD noted in 23 % of cases.…”
Section: Resultsmentioning
confidence: 72%